2020
DOI: 10.1002/cti2.1147
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterisation of NKp44‐based chimeric antigen receptors that confer T cells with NK cell‐like specificity

Abstract: Objectives One of the reasons as to why chimeric antigen receptors (CAR)‐T cell therapy for malignancies other than CD19‐ or BCMA‐positive tumors has yet to produce remarkable progress is the paucity of targetable antigens. NKp44 is only expressed by activated natural killer cells and detects a variety of transformed cells, while it reportedly does not react with normal tissues. The aim of this study is to develop CAR‐T cell that can target multiple types of tumor cells. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The MSCV-IRES-GFP vector, pEQ-PAM3(-E), and pRDF plasmids were obtained from St. Jude Vector Development and Production Shared Resource. Various NKp44-based CAR genes with structural and functional diversity have been developed in our laboratory [17] . The CD19-targeted 4-1BB co-stimulated CAR gene has been reported previously [18] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSCV-IRES-GFP vector, pEQ-PAM3(-E), and pRDF plasmids were obtained from St. Jude Vector Development and Production Shared Resource. Various NKp44-based CAR genes with structural and functional diversity have been developed in our laboratory [17] . The CD19-targeted 4-1BB co-stimulated CAR gene has been reported previously [18] .…”
Section: Methodsmentioning
confidence: 99%
“…NKp44 (also known as NCR2) is an NCR that binds to several ligands on the surface of tumor cells or virally infected cells, including a peculiar isoform of mixed-lineage leukemia protein-5 (MLL5), proliferating cell nuclear antigen, heparan sulfate proteoglycans, nidogen-1, and platelet-derived growth factor-DD [16] . Recently, we developed a novel CAR that targets NKp44 ligands and reported that T cells transduced with this CAR showed antitumor effects against various pediatric solid tumors, including some sarcomas [17] . Ligands for NKp44 are only expressed in malignant tumor cells, and not in normal tissues [16] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that hinge and transmembrane domains can alter the functionality of a CAR by regulating the threshold and amount of CAR signaling, respectively [ 51 , 52 ]. Moreover, they affect the expression levels of the CAR and thereby the antigen recognition [ 53 ].…”
Section: Precise Design For a Functional Car Structurementioning
confidence: 99%
“…These were effective in mouse models of multiple myeloma and ovarian cancer expressing stress ligands recognized by NKG2D [ 162 , 163 , 164 ] but a phase I clinical trial showed limited NKG2Dζ CAR-T cell expansion and persistence [ 165 ], indicating that improvements are likely to be required for clinical viability. Others have investigated similar fusions using NKp44 and NKp30 [ 166 ], activating receptors that associate with DAP12 or ζ through their TM domains, respectively [ 25 ], to endow T cells with NK-like specificity. A related approach has been used to generate scFv-based CARs with the spacer and TM domains from activating NK cell receptor (killer cell immunoglobulin like receptor, two Ig domains and short cytoplasmic tail 2, KIR2DS2 )—KIR-CARs [ 167 ], which assemble with DAP12 through their TM domains [ 61 , 62 , 168 ] ( Figure 3 ).…”
Section: Functional Consequences Of Car Design and Structurementioning
confidence: 99%